2018
DOI: 10.1186/s12887-018-1312-7
|View full text |Cite
|
Sign up to set email alerts
|

Otologic, audiometric and speech findings in patients undergoing surgery for cleft palate

Abstract: BackgroundAlthough considerable progress has been made in the last 30 years in the treatment of cleft palate (CP), a multidisciplinary approach combining examinations by a paediatrician, maxillofacial surgeon, otolaryngologist and speech and language pathologist followed by surgical operation is still required. In this work, we performed an observational cross-sectional study to determine whether the CP grade or number of ventilation tubes received was associated with tympanic membrane abnormalities, hearing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It has been proven that the results obtained in our research are, to a certain level, compatible with the results obtained in other research, but also different at times. Kaewkumsan et al,[16], who examined the degree of hypernasality and formation of an oronasal fistula in 40 patients, aged between 5 and 6,9 years, with non-syndromic cleft palate with or without cleft lip, established that the patients with cleft Class IV and Class III (according to the Veau classification) had a higher total score for hypernasality than patients with Class I. Garcia-Vaquero et al, [17] conducted research about the hearing and speech of 121 patients aged above 6 who had already undergone intervention of the cleft palate. Among other things they also examined the relation between Veau classification and hypernasality.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that the results obtained in our research are, to a certain level, compatible with the results obtained in other research, but also different at times. Kaewkumsan et al,[16], who examined the degree of hypernasality and formation of an oronasal fistula in 40 patients, aged between 5 and 6,9 years, with non-syndromic cleft palate with or without cleft lip, established that the patients with cleft Class IV and Class III (according to the Veau classification) had a higher total score for hypernasality than patients with Class I. Garcia-Vaquero et al, [17] conducted research about the hearing and speech of 121 patients aged above 6 who had already undergone intervention of the cleft palate. Among other things they also examined the relation between Veau classification and hypernasality.…”
Section: Discussionmentioning
confidence: 99%
“…Average age was reported differently amongst the studies, organized either by age at first tube placement, age at lip or palate repair, age at time of study, and age at myringoplasty. Study subjects originated from 13 countries: Canada (Knapik and Saliba, 2012), Finland (Klockars and Rautio, 2012; Lehtonen et al, 2016), France (Rieu-Chevreau et al, 2019), Germany (Reiter et al, 2009), Japan (Kobayashi et al, 2012; Inoue et al, 2020), Taiwan (Yang et al, 2019), Turkey (Kuşcu et al, 2015), South Korea (Ahn et al, 2012), Spain (Garcia-Vaquero et al, 2018), Sweden (Tengroth et al, 2017), Switzerland (Ezzi et al, 2015; Kapitanova et al, 2018), the United Kingdom (Andrews et al, 2004; Merrick et al, 2007; Fitzsimons et al, 2017), and the United States (Goudy et al, 2006; Brgoch et al, 2015; Imbery et al, 2017; Kim et al, 2017; Shaffer et al, 2018; Koempel et al, 2021). More than half (13/23) of these studies were conducted using a retrospective cohort study design; the remaining studies consisted of 4 retrospective case series (Merrick et al, 2007; Imbery et al, 2017; Tengroth et al, 2017; Koempel et al, 2021), 3 cross-sectional studies (Andrews et al, 2004; Brgoch et al, 2015; Garcia-Vaquero et al, 2018), 2 case-control studies (Merrick et al, 2007; Inoue et al, 2020), and 1 prospective cohort study (Kobayashi et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, no data was presented regarding the reason for additional VTI in relation to hearing or speech outcomes. The remaining 2 studies also failed to investigate timing of VTI in relation to hearing and speech, and consequently, provided no insight into our main outcome measure (Andrews et al, 2004; Garcia-Vaquero et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the type of cleft palate has been reported to have no association with the number of ventilation tube insertions. 6 Children with cleft palate are more prone to otitis media with effusion (OME) than children without cleft palate. Previous studies reported that children with cleft palate had an onset of OME in infancy with prolonged effusion, higher incidence of complications and hearing loss from chronic OME.…”
Section: Introductionmentioning
confidence: 99%